DESIGN, SIMULATION AND CONTROL OF A MIST EXTRACTOR FOR THREE-PHASE SEPARATION - Rodríguez, José Luis Mora (Journal of Posthumanism, 2025)
The present study demonstrates the conceptualization, computer-aided design, mechanical calculation, and empirical assessment of a mist extractor, with the objective of enhancing the efficacy of wet gas filtration from oil wells. The study’s primary objective is the structural analysis of various eye events (i.e., rhombic, square, circular, and rhombic) employing ASME regulatory criteria and finite element methods (FEM). This approach is undertaken to ascertain their mechanical strength and behavior under internal operating conditions of up to 100 PSI. Failure theories, including those proposed by Von Mises and Tresca, are employed to calculate safety factors that exceed one unit, thereby ensuring the structural integrity of the material.In the experimental stage, progressive pressure, temperature, and relative humidity decreased, thereby confirming its effectiveness in capturing liquid particles and improving the quality of the resulting dry gas. The findings suggest that the recommended designs offer a substantial approach to minimizing the requirement for additional equipment in a series, thereby conferring economic and spatial advantages for hydrocarbon processing systems.